Intra and Postoperative Advantages of Laparoscopy in the Treatment of Complicated Appendicitis - Andrej Nikolovski; Cemal Ulusoy (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Sciendo, 2022)
Aim: To determine and define the advantages of the laparoscopic appendectomy in the treatment of complicated appendicitis by comparing it with the open appendectomy. Material and Methods: In this prospective interventional clinical study we compared the intraoperative data and the postoperative outcome of 77 patients presented with complicated appendicitis, operated with open and laparoscopic appendectomy within a period of 20 months. One surgeon performed all of the laparoscopic procedures and two other senior surgeons performed the open procedures. Results: Operative time was shorter in the laparoscopic group (p = 0.033). Conversion rate was 2.3%. Overall postoperative morbidity was 25.97%. There was one operative revision due to postoperative small bowel obstruction in the laparoscopic group. Appendicular stump leakage occurred in one patient in the open group. One intra-abdominal abscess occurred in the laparoscopic group (p = 0.38). Wound infection occurred only in the open group (p = 0.018). Length of stay was shorter in the laparoscopic group (p = 0.0052). One patient from the laparoscopic group was readmitted. Conclusions: Laparoscopy is a reliable method in the treatment of complicated appendicitis. It offers a shorter operative time, low conversion rate, an acceptable rate of major postoperative complications and a shorter length of stay.
Keywords: appendectomy; complicated appendicitis; laparoscopy